ANALISIS PENGELOLAAN KEUANGAN USAHA KECIL MIKRO DAN MENENGAH DENGAN ECONOMIC ENTIY CONCEPT - Tommy Munaf; Rohmat Mahfuddin; Nur Hasanah (STIE PEMBANGUNAN TANJUNGPINANG, 2022)
Financial management in Micro, Small and Medium Enterprises is often neglected by MSME business actors, especially those related to the implementation of correct financial and accounting management. The problems that arise are due to the knowledge and information of MSME actors as well as the problem of the Carindo Jaya Semesta Shop which is still a very limited understanding of accounting and the educational background of the MSME actors In accounting, the economic entity concept is an ideal concept for Micro, Small and Medium Enterprises, because by using this concept, Micro and Medium Enterprises will know the actual operating profit of the business.The results showed that the Carindo Jaya Semesta Store Business tried to apply the economic entity concept in its business even though it was not perfect, with this application the Carindo Jaya Semesta Store Business also made financial reports even though it was not in accordance with SAK EMKM